Core topics in operating department practice anaesthesia and critical care - Smith, Brian 1965- (Cambridge University Press, 2007)
Recent changes in medical roles and responsibilities have raised the profile of Operating Department Practitioners (ODPs). The level of knowledge is vast, and exams must be taken working towards statutory registration. This is the first in a series of three books providing comprehensive information for healthcare staff working in the operating department. Topics covered include anaesthesia, critical care, post-interventional care, enhancing care delivery, professional practice, leadership and resource management. The clear and concise format is ideally suited to study, qualification and for continued reference during practice. Written by specialists with a wealth of knowledge and experience, and incorporating problem-based learning using case studies, this book will be essential reading for ODPs and theatre nurses throughout the UK, in Australia where the same structures have been adopted, and worldwide for all professionals working in operating departments.